Influence of Nd Substitution for Ca on Formation of 2223 Phase in the Superconductors (Bi,Pb)-Sr-Ca-Cu-O System: (Bi1.4Pb0.6)Sr2(Ca2-xNdx)Cu3O10+δ - M . Sumadiyasa Sumadiyasa (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
The influence of Nd substitutions for Ca on formation of 2223 phase in the superconductors (Bi,Pb)-Sr-Ca-Cu-O system : (Bi1.4Pb0.6)Sr2(Ca2-xNdx)Cu3O10+δ has been studied. Samples were made by solid state reaction methods, with sintering temperature at 860oC for 40 hours continuously in air atmosphere. From the XRD characterization it is revealed that the samples are poly crystals and the volume fraction of Bi-2223 phase is less than 45%. All of samples show Meissner effect weakly on 77 K, which is indicate that in the samples has formed few superconducting high-Tc phase. This result is in accords with of the resistivity as function of temperature measurement, show that the Tcon-set at 88 K - 107 K, which is range of the critical temperature (Tc) of the Bi-2212 phase and Bi-2223 phase.